Management of Angioedema and Mucositis as Oral Manifestations of Juvenile Systemic Lupus Erythematosus - Manuel Dwiyanto Hardjo lugito (Universitas Muhammadiyah Yogyakarta, 2025)
Angioedema and mucositis are rare in juvenile systemic lupus erythematosus (jSLE) and increase morbidity and mortality in an individual under 18 years. This case report aims to describe the management of an 11-year-old female patient with a history of jSLE, presenting with swelling of her lip, difficulty in speaking, oral pain since a month ago, and self-medicating, which led to the swelling becoming worse. Full blood count, immunology, and antigen laboratory examination indicated anemia normocytic normochromic, leukopenia, hypoalbuminemia, vitamin D deficiency, proteinuria, neonatal lupus erythematosus, and Sjogren’s syndrome. Methylprednisolone, mycophenolate mofetil, and hydroxychloroquine sulfate were given by the pediatrician. Medications consisted of topical application of 0.1%triamcinolone acetonide in orabase for angioedema and mucositis, benzydamine hydrochloride oral rinse before meals, chlorhexidine gluconate and 0.025% hyaluronic acid mouthwash after meals and before bed. Oral complaints and lesions have improved within 10 days. High caution, specific examinations to determine the type of angioedema, collaboration with pediatric rheumatologists, and systemic treatment of SLE must be supported by topical therapy to treat AE and mucositis, which are oral manifestations of SLE.